Análise comparativa de representação arquivística: acervo Romanov e de Prokudin-Gorskii - FERREIRA, Yasmin Yura da Silva (2023)
The present work analyzed the relationship of archival standards in digital repositories held in the US Library of Congress, in the “Prokudin-Gorskii Collection” and at Yale University in the “Romanov Collection”, both photographic albums related to tsarist Russia between the years 1890 and 1915, respectively linked to the Russian photographer Prokudin-Gorskii and Tsar Nicholas II. The research initially discussed aspects related to representation/description and its use in photographic supports. Subsequently, based on the analysis of a photograph taken from each collection, the description elements of the General International Standard for Archival Description – ISAD(G) were related to those of the selected repositories, identifying the context and structure of representation. Thus, it was verified that the repositories express significant similarities in relation to ISAD(G), even if their representation/description was not elaborated using the standard, therefore, “Prokudin-Gorskii Collection” presenting greater approximations with ISAD(G), with 6 areas and 14 elements interrelated with their detailing content. The research also identified the possibility of using data collected in national repositories related to photographic description.